Recent Legal Developments: Criminal Justice Decisions of the United States Supreme Court, 2023 Term - Hemmens, Craig (Criminal justice review, 2025)
In this paper, we review and analyze the criminal justice-related decisions of the 2023 term of the United States Supreme Court. We also provide a summary of the Court's voting patterns and opinion authorship. Sixteen of the Court's 59 decisions touched on criminal justice. There were significant decisions involving the Second Amendment, the Sixth Amendment, and federal criminal statutes. Each of these is discussed in turn.